Challenges Against Implementation of Social Studies Curriculum for Moral Development in Nigerian Junior Secondary Schools: Ilorin as Case Study - Asmau, Abdul Kabir Imam (International Journal Pedagogy of Social Studies, 2023)
This study explores the challenges against the implementation of Junior Secondary School Social Studies curriculum for moral development in Ilorin, Kwara State, Nigeria. The study is a qualitative one that employed a case study research approach. The qualitative tools of interview and observation were used to gather data to address the research questions. A total of 12 teachers with a variety of years of experience were selected to participate in the study. Purposive sampling procedures were used to select the sample for the study. For data analysis, teacher perspectives were gathered and examined for emerging themes and trends among teachers in their perspectives. The result showed that the junior secondary school Social Studies curriculum has content and teaching approaches that are suitable for students’ moral development. Equally, the study revealed that class congestion, inadequate and inappropriate resource materials, wide syllabus and examination pressure were among the factors hindering effective implementation of the curriculum for moral inculcation. Some recommendations were also offered for the improvement of the Social Studies curriculum.